2002
DOI: 10.1074/jbc.m207097200
|View full text |Cite
|
Sign up to set email alerts
|

A Structure-based Mutational Analysis of Cyclophilin 40 Identifies Key Residues in the Core Tetratricopeptide Repeat Domain That Mediate Binding to Hsp90

Abstract: Cyclophilin 40 (CyP40) is a tetratricopeptide repeat (TPR)-containing immunophilin and a modulator of steroid receptor function through its binding to heat shock protein 90 (Hsp90). Critical to this binding are the carboxyl-terminal MEEVD motif of Hsp90 and the TPR domain of CyP40. Two different models of the CyP40-MEEVD peptide interaction were used as the basis for a comprehensive mutational analysis of the Hsp90-interacting domain of CyP40. Using a carboxyl-terminal CyP40 construct as template, 24 amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 49 publications
6
71
0
Order By: Relevance
“…The most conserved amino acid residues in the FCBP TPRs are indicated by all arrowheads. Residues that are known to interact with the MEEVD sequence of Hsp90, based on structural studies of CYN and FKBP TPRs (Cliff et al 2006;Scheufler et al 2000;Ward et al 2002;Wu et al 2004), are specifically indicated with closed arrowheads (detailed in Results); note that they are also among the most highly conserved, supporting the functional importance of a potential FCBP TPRHsp90 interaction…”
Section: Gammaproteobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The most conserved amino acid residues in the FCBP TPRs are indicated by all arrowheads. Residues that are known to interact with the MEEVD sequence of Hsp90, based on structural studies of CYN and FKBP TPRs (Cliff et al 2006;Scheufler et al 2000;Ward et al 2002;Wu et al 2004), are specifically indicated with closed arrowheads (detailed in Results); note that they are also among the most highly conserved, supporting the functional importance of a potential FCBP TPRHsp90 interaction…”
Section: Gammaproteobacteriamentioning
confidence: 99%
“…The binding exhibits various degrees of specificity between the two partners; Hsp90, for example, is preferred over Hsp70 to bind to the TPRs of the large FKBPs (Assimon et al 2015;Guy et al 2015). In particular, peptide-TPR co-crystal structure and mutational analysis have established that the invariant C-terminal pentapeptide, MEEVD, of Hsp90 (Gupta 1995) interacts with specific residues that are common to the TPRs of long FKBPs and CYNs (Assimon et al 2015;Cliff et al 2006;Scheufler et al 2000;Ward et al 2002;Wu et al 2004). The residues, found to be absolutely essential for MEEVD binding, are: K5, N9 in TPR1, N6 in TPR2, and K2, R6 in TPR3.…”
Section: Gammaproteobacteriamentioning
confidence: 99%
“…hsp90 is also required for protein translocation into mitochondria (Young et al, 2003) and peroxisomes (Crookes and Olsen, 1998). The trafficking functions of hsp90 depend on cytoskeletal elements (Galigniana et al, 1998(Galigniana et al, , 2002Pratt et al, 1999) and involve specific interactions between C-terminal sequences of hsp90 and tetratricopeptide repeat (TPR) domains in several effector molecules (Chen et al, 1996;Young et al, 1998;Russell et al, 1999;Scheufler et al, 2000;Ward et al, 2002). TPR domains are involved in a variety of cellular functions, including protein transport and targeting (for review, see Blatch and Lassle, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the sequence and three-dimensional structures of TPR domain and TPR-recognition motif in Hsp90 are conserved in Plasmodium parasite and their molecular basis of the interaction between PfFKBP35-TPR and the Hsp90 pentapeptide are similar to the known TPR domain and Hsp90 interactions. 16,24,25 Despite the similarity, however, possible specificity of this interaction could also be understood as seen in Hsp70-Hop-Hsp90 complex. 16 Hop has two TPR domains TPR2A1 and TPR1 that interact exclusively with Hsp90 and Hsp70, respectively.…”
Section: Hsp90 Pentapeptide Binding To Pffkbp35-tprmentioning
confidence: 99%
“…The MEEVD pentapeptide present at the C-terminus of Hsp90 (hereafter Hsp90 pentapeptide), which is conserved in all eukaryotes, serves as a TPR recognition motif. 16,[23][24][25] Hsp90 orthologue of P. falciparum (PfHsp90, PF07_0029) also contains the invariant MEEVD at the C-terminal. 26,27 It has been shown that the TPR domain of PfFKBP35 (hereafter PfFKBP35-TPR) associates with the PfHsp90.…”
Section: Introductionmentioning
confidence: 99%